2021
DOI: 10.3389/fphar.2021.739644
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Efects of the Topical of “Sanse Powder” Essential Oils Nanoemulsion on Knee Osteoarthritis in Rats by Targeting the ERS/TXNIP/NLRP3 Signaling Axis

Abstract: Purpose: Our recent research is dedicated to finding effective drugs for the treatment of knee osteoarthritis (KOA) from traditional Chinese medicine and trying to make full use of modern science and technology to uncover the mechanisms and targets behind them. Synovial inflammation is one of the key pathological features of KOA, and a growing number of researchers realize that early intervention of synovial inflammation may be able to reverse disease progression. The close association of traditional natural p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In their study, Peng et al showed that 5,7,3′,4′‐tetramethoxyflavone restored cholesterol dysregulation by mediating SIRT1/FOXO3a/ABCA1 signaling in OA‐affected chondrocytes (Peng et al, 2021). Moreover, the study by Liu et al demonstrated that “Sanse Powder” essential oils had considerable treatment effects on knee OA by targeting the ERS/TXNIP/NLRP3 signaling axis (Liu et al, 2021). In the review by Siddiqi et al, the authors summarized the functions of diverse ginsenosides and concluded that the therapeutic properties of ginsenosides can be exerted via different molecular agents (Siddiqi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Peng et al showed that 5,7,3′,4′‐tetramethoxyflavone restored cholesterol dysregulation by mediating SIRT1/FOXO3a/ABCA1 signaling in OA‐affected chondrocytes (Peng et al, 2021). Moreover, the study by Liu et al demonstrated that “Sanse Powder” essential oils had considerable treatment effects on knee OA by targeting the ERS/TXNIP/NLRP3 signaling axis (Liu et al, 2021). In the review by Siddiqi et al, the authors summarized the functions of diverse ginsenosides and concluded that the therapeutic properties of ginsenosides can be exerted via different molecular agents (Siddiqi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting overactive canonical PERK/TXNIP/NLRP3 signaling has emerged as a promising treatment strategy for KOA ( Liu et al, 2021 ; Tian et al, 2023 ). In addition, based on the limitations of previous studies, we are also in search of drug monomers that can suppress the NLRP3 inflammasome to mitigate synovitis and fibrosis in KOA ( Zhang et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…The NLRP3 inflammasome is activated in OA and promotes the maturation and secretion of IL-1β and IL-18 [ 32 ]. Increasing studies have shown that inhibition of NLRP3 inflammasome activation in OA articular cartilage can reduce the inflammatory response and thus reduce articular cartilage injury [ 7 9 ]. Ni et al showed that the NLRP3 inhibitor MCC950 can alleviate articular cartilage degradation in a mouse OA model [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies have shown that NLRP3 protein is significantly upregulated in OA cartilage. Therefore, NLRP3 inhibitors might serve as a promising strategy for OA treatment by inhibiting excessive inflammatory responses [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%